2022
DOI: 10.1038/s41467-022-31838-8
|View full text |Cite
|
Sign up to set email alerts
|

Protection of COVID-19 vaccination and previous infection against Omicron BA.1, BA.2 and Delta SARS-CoV-2 infections

Abstract: Given the emergence of the SARS-CoV-2 Omicron BA.1 and BA.2 variants and the roll-out of booster COVID-19 vaccination, evidence is needed on protection conferred by primary vaccination, booster vaccination and previous SARS-CoV-2 infection by variant. We employed a test-negative design on S-gene target failure data from community PCR testing in the Netherlands from 22 November 2021 to 31 March 2022 (n = 671,763). Previous infection, primary vaccination or both protected well against Delta infection. Protection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 19 publications
6
84
1
Order By: Relevance
“…We found that the Omicron variant was associated with a higher proportion of infections in boosted individuals compared to both unvaccinated and fully vaccinated individuals, however, we could not find a difference in the proportion of infections between Delta and Omicron when comparing individuals who completed their primary vaccination schedule to unvaccinated individuals. In contrast to this, other studies found that vaccine effectiveness was considerably lower for Omicron versus Delta when comparing both boosted and fully vaccinated individuals to unvaccinated subjects (Andeweg et al, 2022;Jalali et al, 2022;Lyngse et al, 2022;Tseng et al, 2022). This discrepancy could be explained by the effect of waning immunity since most individuals who completed their primary vaccination schedule during our study period received their second dose >6 months before the first positive PCR, a time after which vaccine protection against infection decreases significantly against both the Delta and Omicron variants (Gilboa et al, 2022;Goldberg et al, 2022).…”
Section: Discussioncontrasting
confidence: 85%
“…We found that the Omicron variant was associated with a higher proportion of infections in boosted individuals compared to both unvaccinated and fully vaccinated individuals, however, we could not find a difference in the proportion of infections between Delta and Omicron when comparing individuals who completed their primary vaccination schedule to unvaccinated individuals. In contrast to this, other studies found that vaccine effectiveness was considerably lower for Omicron versus Delta when comparing both boosted and fully vaccinated individuals to unvaccinated subjects (Andeweg et al, 2022;Jalali et al, 2022;Lyngse et al, 2022;Tseng et al, 2022). This discrepancy could be explained by the effect of waning immunity since most individuals who completed their primary vaccination schedule during our study period received their second dose >6 months before the first positive PCR, a time after which vaccine protection against infection decreases significantly against both the Delta and Omicron variants (Gilboa et al, 2022;Goldberg et al, 2022).…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, vaccine effectiveness against the BA.2 lineage was lower than against the BA.1 lineage, consistent with a recent US based electronic health record study, 15 but different from recent studies from the United Kingdom and the Netherlands that suggested similar vaccine effectiveness against BA.2 and BA.1. 37 38 The use of viral whole genome sequencing in the current study enabled genetic characterization of many of the viruses. Importantly, 56% of the sequenced BA.2 viruses in this study had a BA.2.12.1 sequence, which has enhanced immune escape features compared with earlier omicron lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the timely development of effective and safe COVID-19 vaccines, hesitancy to get vaccinated emerged as a major hindrance to preventive efforts [ 8 , 9 , 10 ]. In addition, waning immunity following infection or vaccination and the continuous emergence of SARS-CoV-2 variants with immune escape potential underlined the necessity of booster doses of COVID-19 vaccines [ 11 , 12 , 13 ]. Booster dose can be defined as an extra dose of vaccine administered following the completion of a primary vaccination series [ 14 ].…”
Section: Introductionmentioning
confidence: 99%